Vulgäre und derbe Idiome im Deutschen. Einige Bemerkungen zu ihrer Bedeutung, Frequenz, Stilmarkierung und ihrem Gebrauch - DZIUREWICZ, ELŻBIETA (Glottodidactica, 2019)
In the context of this article, the crude and vulgar idioms mentioned in Duden-11 “Redewendungen” will be examined in terms of their motivation, meaning, frequency, style marking and their usage. First, they will be extracted from this dictionary and examined according to their origins. Next, they will be categorized concerning their subjects. Furthermore, the style tags used in the dictionary will be tested. This will be done by contrasting them to reference corpora before carrying out a survey among native speakers. Finally, a list of common, relatively frequent idioms will be created, which can then be used primarily in foreign language didactics.